3-Deoxysappanchalcone Inhibits Skin Cancer Proliferation by Regulating T-Lymphokine-Activated Killer Cell-Originated Protein Kinase in vitro and in vivo - Fu, Xiaorong; Zhao, Ran; Yoon, Goo; Shim, Jung-Hyun; Choi, Bu Young; Yin, Fanxiang; Xu, Beibei; Laster, Kyle Vaughn; Liu, Kangdong; Dong, Zigang; Lee, Mee-Hyun (Frontiers in Cell and Developmental Biology, 2021)
Background Skin cancer is one of the most commonly diagnosed cancers worldwide. The 5-year survival rate of the most aggressive late-stage skin cancer ranges between 20 and 30%. Thus, the discovery and investigation of novel target therapeutic agents that can effectively treat skin cancer is of the utmost importance. The T-lymphokine-activated killer cell-originated protein kinase (TOPK), which belongs to the serine-threonine kinase class of the mitogen-activated protein kinase kinase (MAPKK) family, is highly expressed and activated in skin cancer. The present study investigates the role of 3-deoxysappanchalcone (3-DSC), a plant-derived functional TOPK inhibitor, in suppressing skin cancer cell growth. Purpose In the context of skin cancer prevention and therapy, we clarify the effect and mechanism of 3-DSC on different types of skin cancer and solar-simulated light (SSL)-induced skin hyperplasia. Methods In an in vitro study, western blotting and in vitro kinase assays were utilized to determine the protein expression of TOPK and its activity, respectively. Pull-down assay with 3-DSC and TOPK (wild-type and T42A/N172 mutation) was performed to confirm the direct interaction between T42A/N172 amino acid sites of TOPK and 3-DSC. Cell proliferation and anchorage-independent cell growth assays were utilized to determine the effect of 3-DSC on cell growth. In an in vivo study, the thickness of skin and tumor size were measured in the acute SSL-induced inflammation mouse model or SK-MEL-2 cell-derived xenografts mouse model treated with 3-DSC. Immunohistochemistry analysis of tumors isolated from SK-MEL-2 cell-derived xenografts was performed to determine whether cell-based results observed upon 3-DSC treatment could be recapitulated in vivo. Results 3-DSC is able to inhibit cell proliferation in skin cancer cells in an anchorage-dependent and anchorage-independent manner by regulation of TOPK and its related signaling pathway in vitro. We also found that application of 3-DSC reduced acute SSL-induced murine skin hyperplasia. Additionally, we observed that 3-DSC decreased SK-MEL-2 cell-derived xenograft tumor growth through attenuating phosphorylation of TOPK and its downstream effectors including ERK, RSK, and c-Jun. Conclusions Our results suggest that 3-DSC may function in a chemopreventive and chemotherapeutic capacity by protecting against UV-induced skin hyperplasia and inhibiting tumor cell growth by attenuating TOPK signaling, respectively.